2020
DOI: 10.21101/cejph.a6182
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected risk factors in cardiovascular diseases in two different populations of the Czech Republic

Abstract: Objectives: The aim of this work is to compare the current prevalence of selected risk factors in cardiovascular diseases in the Czech general population in a particular region with a selected population of Czech soldiers in a particular military unit. Methods: Within medical preventive examinations, data from 684 civilians aged between 30-60 years were obtained (405 men and 279 women). Within compulsory medical preventive examinations, data from 659 soldiers from a particular military unit aged between 30-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…The prevalence of DM in other studies was much lower compared to that observed among EoUS in this study [36]. et al [9] found significantly worse anthropometric and biochemical parameters in the selected male military cohort compared to a male civilian cohort. Smoking is one of the most significant cardiovascular risk factors, associated with an increased risk of developing a first myocardial infarction as well as an increased risk of cancer, respiratory diseases, and higher all-cause mortality [28][29][30].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The prevalence of DM in other studies was much lower compared to that observed among EoUS in this study [36]. et al [9] found significantly worse anthropometric and biochemical parameters in the selected male military cohort compared to a male civilian cohort. Smoking is one of the most significant cardiovascular risk factors, associated with an increased risk of developing a first myocardial infarction as well as an increased risk of cancer, respiratory diseases, and higher all-cause mortality [28][29][30].…”
Section: Discussioncontrasting
confidence: 73%
“…However, a study by Gielerak et al [8] showed that Polish soldiers present with multiple cardiovascular (CV) risk factors, as seen in the general population. In a Czech study, male soldiers were burdened with significantly more CV risk factors compared to the civilian population [9]. Zimmermann demonstrated that CV risk factors result in high mortality rates among law enforcement personnel [10].…”
Section: Introductionmentioning
confidence: 99%